CoFe2O4 embedded bacterial cellulose for flexible, biodegradable, and self-powered electromagnetic sensor. (November 2022) - Chen, Kun; Li, Yifan; Du, Zhuolin; Hu, Sanming; Huang, Jianyu; Shi, Zhijun; Su, Bin; Yang, Guang
Abstract: Self-powered flexible electromagnetic sensors based on flexible magnets are promising to be applied in wearable field. As the core component of motion sensors, flexible magnets are getting growing attentions. However, most reported flexible magnets were fabricated with non-degradable substrate materials via complicated processes. Here, a novel flexible, biodegradable and self-powered electromagnetic sensor was prepared based on CoFe2 O4 -embedded magnetic bacterial cellulose, which is prepared by a facile and economical in-situ co-precipitation paired with a post-process of hot-pressing and magnetizing. Magnetic CoFe2 O4 nanoparticles were synthesized in network structure of degradable bacterial cellulose for flexible composited magnetic films. Degradation experiment demonstrated that the flexible magnetic films degraded completely within 56 h, and the left magnetic materials of CoFe2 O4 nanoparticles could be recycled. The flexible electromagnetic sensors based on composited films were tested in a customized testing platform, manifesting excellent sensing properties and stability. To deeply verify the application potential of the flexible electromagnetic sensors, an intelligent jacket, which was sewn with flexible magnetic film and copper coils was designed. It is capable of monitoring motion signals and distinguishing the motion state, proving that the biodegradable flexible electromagnetic sensor is promising to be utilized in wearable field as a kind of eco-friendly flexible sensor. Graphical Abstract: A novel flexible, biodegradable and self-powered electromagnetic sensor was prepared based on CoFe2 O4 -embedded magnetic bacterial cellulose through economical in-situ co-precipitation methods. Combining with copper coils, the flexible electromagnetic sensor was designed as an intelligent jacket which is capable of monitoring motion signals. ga1 Highlights: The CoFe2 O4 nanoparticles 30–40 nm are successfully synthesized on the fibers of BC. Flexible magnetic BC film is able to degraded completely and only eco-friendly CoFe2 O4 nanoparticles are left. The flexible electromagnetic sensor exhibits high stability and the induced voltage is adjusted from 0.17 mV to 6.85 mV. The intelligent jacket composed of flexible magnetic BC film is capable of monitoring human motion activity and motion speed precisely.